2016
DOI: 10.1002/hyp.11001
|View full text |Cite
|
Sign up to set email alerts
|

Throughfall enrichment and stream nutrient chemistry in small headwater catchments with different land cover in southern Chile

Abstract: Land cover changes have a great impact on nitrogen (N) and phosphorous (P) fluxes catchments. In this study, we wanted to compare different land covers: deciduous (D), evergreen (E) (both native forests), and exotic Eucalyptus globulus plantation (EP), affected precipitation, and stream discharge on N and P species concentrations and fluxes, under a low deposition climate in south‐central Chile. For this, we collected bulk precipitation, throughfall, and stream water samples after 41 rainfall events in E and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Although we did not detect significant differences in nutrient concentrations among streams from different successional forest (Figures 3(c,d) and S2), there was a remarkable nutrient enrichment overall, via throughfall water (Table 2), which is highly relevant for ecosystem biogeochemistry (Hervé‐Fernandez et al, 2016; Nelson et al, 2013; Weathers et al, 2001, 2006). Because this study comprised a limited number of rain events at a specific time of the year, results are subject to uncertainties that must be addressed in future long‐term studies (Zhang & Wei, 2021).…”
Section: Discussionmentioning
confidence: 76%
“…Although we did not detect significant differences in nutrient concentrations among streams from different successional forest (Figures 3(c,d) and S2), there was a remarkable nutrient enrichment overall, via throughfall water (Table 2), which is highly relevant for ecosystem biogeochemistry (Hervé‐Fernandez et al, 2016; Nelson et al, 2013; Weathers et al, 2001, 2006). Because this study comprised a limited number of rain events at a specific time of the year, results are subject to uncertainties that must be addressed in future long‐term studies (Zhang & Wei, 2021).…”
Section: Discussionmentioning
confidence: 76%
“…Ochoa‐Tocachi et al () implemented a paired catchment setup and used data from 25 headwater catchments in the tropical Andes to link their hydrological responses to different types of human interventions (i.e., cultivation, afforestation, and grazing) and found that all anthropogenic interventions increased streamflow variability and generated significant reductions in catchment regulation capacity and water yield. Hervé‐Fernandez, Oyarzún and Woelfl () assessed the “two water worlds” theory through a whole year in two catchments, one covered by Eucalyptus nitens and the other by a native evergreen forest, finding that the two water worlds does not apply throughout the year confirming previous hypotheses. In addition their results suggest that E .…”
mentioning
confidence: 76%
“…Eight of the manuscripts tackle the effects of afforestation of grasslands and native forest substitutions and forest management in catchments covered with fast growing forest plantations; two of them approach rainfall partitioning analyses (Silva et al, ; Soto‐Schönherr & Iroumé, ), one analysed throughfall enrichment and stream nutrient chemistry in small headwater catchments (Hervé‐Fernández, Oyarzún, Brumbt, et al, ), two studied the hydrological effects of forest plantation management (Almeida, Smethurst, Siggins, Cavalcante, & Borges, ; Silveira et al, ) and other types of human interventions (Ochoa‐Tocachi et al, ), and one investigated water sources for native and exotic tree species (Hervé‐Fernandez, Oyarzún, & Woelfl, ). Silva et al () studied throughfall patterns in sugarcane and riparian forest to understand the effect of sugarcane age and land use conversion, finding no significant differences between cycles of sugarcane, growth phases, and riparian forest.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the increased root system improves the physical and chemical properties of the surrounding soil (Gao et al, 2009). Vegetation type can affect soil nutrient loss in the basin (Hervé‐Fernandez et al, 2016). Turnbull et al (2011) studied the loss and redistribution of soil N and P caused by runoff in the process of grassland degradation to shrub land and found that in areas dominated by shrubs, N losses were considerably higher than in grass areas.…”
Section: Discussionmentioning
confidence: 99%